Metode Scaffolding dengan Kartu Suku Kata Meningkatkan Kemampuan Membaca Permulaan Siswa Mild Intellectual Disabilities - Astinah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Limited cognitive function students need special learning strategies in formal schools. This study analyzed students with Mild Intellectual Disabilities were based on psychological assessments based on observations, interviews, Binet Intelligence Tests, Curriculum-Based Measurement (CBM) tests, and reports on learning outcomes. Scaffolding method is a learning technique designed to change the support given to students during the learning session by adjusting the level of students' abilities. This study aims to improve reading skills in mild intellectual disabilities students, especially early reading skills. This research method uses a single case experimental design with scaffolding method intervention followed by the use of syllable cards in a 2nd year of elementary school students who comprehended Indonesian language material in class 1 semester I. The data were analyzed descriptively which reported the improvement in the subject's reading ability based on the results of the intervention. The intervention to the subject was preceded by psychoeducation to teachers and parents for the attainment of research objectives. The results showed that the scaffolding method, followed by the use of syllable cards, specifically affected the subject's ability to pronounce letters, read syllables, read words, complete words, write dictated words, and read simple sentences. As a result, the subject shows the ability to read three to five syllables in a word and the subject can read words containing consonants at the end of words. Keywords: Mild Intellectual Disabilities, Scaffolding Method, Syllable Cards, Beginning Reading, Children with Special Needs